The influence of class management on mathematics learning outcomes in algebraic form material - Ulanda, Riska; Siregar, Sakinah Ubudiyah; Pasaribu, Laili Habibah (Universitas Islam Negeri Raden Intan Lampung, 2024)
This research aims to find out the effect of classroom management on the learning outcomes of mathematics in algebra form material. The question is whether there is an influence of classroom management on the results of mathematics learning in algebra form material? This research method uses a descriptive approach with a quantitative method by knowing the value of the influence of classroom management on students' mathematics learning outcomes in algebra form material. Data was obtained using a questionnaire. The written questionnaire instrument consists of 10 questions on the influence of classroom management and 10 questions on the results of students' mathematics learning in algebra form material. Data analysis techniques using descriptive statistics. The results of the study show that the value of the influence of classroom management on students' mathematics learning outcomes in the form of material algebra obtained an average percentage of scores of 88.34% and 84.83% in the category of excellent. Meanwhile, the maximum value of the influence of classroom management on the mathematics learning outcomes of class X students is 91.72% and 91.37% in the very good category. This shows that the value of the influence of classroom management has a strong relationship with the results of students' mathematics learning in algebra form material.